Associations between early home environment and trajectories of disruptive behavior among preschoolers reared in CPS-referred families. (December 2019) - Bick, Johanna; Lipschutz, Rebecca; Lind, Teresa; Zajac, Lindsay; Dozier, Mary
Young children who experience maltreatment are at increased risk for disruptive behavior problems. In high-risk environments, children's difficulties regulating negative emotions and behavior may be an important precursor to later disruptive behavior problems. This longitudinal study examined associations between early home risk factors and trajectories of disruptive behavior in young children in Child Protective Services–involved families. Standardized observations of disruptive behavior, home environment quality, and parenting risk were measured when children ( N = 142) were 36 and 48 months old. Results of multiple indicator latent change models showed that early childhood anger dysregulation decreased over the early preschool period. Early home and parenting risk factors (increased harsh parenting, reduced organization of the home, and decreased parental involvement and responsiveness) were associated with higher baseline values of anger dysregulation at 36 months, but not with change in anger dysregulation over the preschool period. These findings hold important implications for early prevention and intervention for externalizing problems among children in the child welfare system.